An examination of the role of arousal and actual behaviour on commitment towards recycling and environmental preservation. (2017) - Loureiro, Sandra M.C.; Miranda, F. Javier
Recycling and environmental preservation have been a topic of growing interest. However, the way individuals engage in a commitment process to the environment and its consequences are not well-known. In order to contribute to fill this gap, a model was proposed positing that self expression through environmentally proactive behaviours combined with a sense of arousal lead to an affective commitment to recycling and environmental preservation. Findings reveal the importance of energetic arousal to reinforce the self-expression in order to increase the commitment to the environmental preservation. Individuals who have an attitude of concern for the environment when making purchasing decisions tend to be more committed. Finally, committed people are more willing to sacrifice towards the cause and spread the word in favour of the cause. The study has enhanced the understanding of the determinants of recycling behaviour and has implications for schools and governmental agencies in educating and encouraging positive recycling behaviour.